2015
DOI: 10.1016/j.chembiol.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for β-Carboline Alkaloid Production by the Microbial Homodimeric Enzyme McbB

Abstract: The β-carboline (βC) alkaloids occur throughout nature and exhibit diverse biological activities. In contrast to βC alkaloid synthesis in plants, the biosynthesis in microorganisms remains poorly understood. The recently reported McbB from Marinactinospora thermotolerans is a novel enzyme proposed to catalyze the Pictet-Spengler (PS) reaction of L-tryptophan and oxaloacetaldehyde to produce the βC scaffold of marinacarbolines. In this study, we solved the crystal structure of McbB complexed with L-tryptophan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 27 publications
2
22
0
3
Order By: Relevance
“…The current in vitro studies by Mori et al (2015) confirmed that purified McbB converts L-tryptophan and oxaloacetaldehyde into the b-carbolines 1 (major product) and 2 (minor product). They also demonstrated that a variety of other simpler aldehydes, such as acetaldehyde and isobutyraldehyde, served as alternate substrates, but the non-enzymatic oxidation/ decarboxylation steps that aromatize the newly formed ring did not take place.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…The current in vitro studies by Mori et al (2015) confirmed that purified McbB converts L-tryptophan and oxaloacetaldehyde into the b-carbolines 1 (major product) and 2 (minor product). They also demonstrated that a variety of other simpler aldehydes, such as acetaldehyde and isobutyraldehyde, served as alternate substrates, but the non-enzymatic oxidation/ decarboxylation steps that aromatize the newly formed ring did not take place.…”
supporting
confidence: 85%
“…The C domain of the nonribosomal peptide synthetase SfmC has also been reported to catalyze iterative Pictet-Spengler reactions in the biosynthesis of saframycin A, although structural information on this enzyme is absent (Koketsu et al, 2010). In this issue, Mori et al (2015) report the structural elucidation of a new type of Pictet-Spenglerase, McbB, which is involved in the biosynthesis of b-carboline alkaloids (Mori et al, 2015). While the amine-containing substrate in this reaction is provided by L-tryptophan, the structure of McbB is unrelated to that of either strictosidine synthase or norcoclaurine synthase, and thus it represents a novel evolutionary answer to the answer of Pictet-Spenglerase catalysis.…”
mentioning
confidence: 95%
“…Pictet–Spenglerases have also been identified in bacterial secondary metabolism151617. The plant enzymes have a central role in engineered microbial systems for the production of alkaloids1819202122.…”
mentioning
confidence: 99%
“…McbB aus Marinactinospora thermotolerans katalysiert die Kondensation von l ‐Tryptophan ( 70 ) mit Oxaloacetaldehyd ( 71 ) zu β‐Carbolin ( 72 ). Obwohl McbB eine andere Proteinfaltung besitzt als Strictosidin‐Synthase, wurde Glu97 anhand von Untersuchungen zur ortsspezifischen Mutagenese von McbB als katalytisch wirksamer Rest identifiziert . Dieser strukturelle Hinweis spricht dafür, dass die Katalysen von Kondensationsreaktionen durch McbB und Strictosidin‐Synthase wahrscheinlich nach ähnlichen Mechanismen ablaufen.…”
Section: Kondensationsreaktionenunclassified